PENERAPAN METODE NAÏVE BAYES DALAM KLASIFIKASI KABUPATEN/KOTA DI SUMATERA UTARA BERDASARKAN PRODUKTIVITAS PANGAN PADI - Sulaiman Ananda Harahap; Rima Aprilia; Riri Syafitri Lubis (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Rice production in North Sumatra Province from January to December 2021 reached approximately 2 million tons of GKG, or a decrease of around 36.36 thousand tons of GKG (1.78 percent) compared to 2020. The decline in rice production also had an impact on the level of rice productivity and also had an impact on rice production. In the economic sector, it is necessary to classify rice productivity in order to support the increase in future rice production in North Sumatra Province. The purpose of this study was to determine the classification of district/city rice productivity using the Naïve Bayes method. This study uses 20 districts/cities as training data and 12 districts/cities as testing data. From the test results, 6 regencies/cities are classified with high level and 26 regencies/cities are classified with low level. The accuracy results obtained are 75% where this accuracy is a fairly good result in classification